2019
DOI: 10.3390/agronomy9070343
|View full text |Cite
|
Sign up to set email alerts
|

ACC Deaminase Producing PGPR Bacillus amyloliquefaciens and Agrobacterium fabrum along with Biochar Improve Wheat Productivity under Drought Stress

Abstract: Drought stress retards wheat plant’s vegetative growth and physiological processes and results in low productivity. A stressed plant synthesizes ethylene which inhibits root elongation; however, the enzyme 1-Aminocyclopropane-1-Carboxylate (ACC) deaminase catabolizes ethylene produced under water stress. Therefore, the ACC deaminase producing plant growth promoting rhizobacteria (PGPR) can be used to enhance crop productivity under drought stress. Biochar (BC) is an organically active and potentially nutrient-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(77 citation statements)
references
References 70 publications
4
66
1
6
Order By: Relevance
“…Similarly, in the current study, the chlorophyll a, chlorophyll b, total chlorophyll, carotenoids, and anthocyanin were significantly increased in response to a higher application rate of PLB (2%; Table 3). We did not find an exactly comparable study of same feedstock and crop; our findings can be compared to pot [75] and field [26] studies' findings. Moreover, a reduction (or antagonistic relation) of plant lycopene contents in response to PLB application also indicates the mitigation of the experimental nutritional stress in this study.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…Similarly, in the current study, the chlorophyll a, chlorophyll b, total chlorophyll, carotenoids, and anthocyanin were significantly increased in response to a higher application rate of PLB (2%; Table 3). We did not find an exactly comparable study of same feedstock and crop; our findings can be compared to pot [75] and field [26] studies' findings. Moreover, a reduction (or antagonistic relation) of plant lycopene contents in response to PLB application also indicates the mitigation of the experimental nutritional stress in this study.…”
Section: Discussioncontrasting
confidence: 88%
“…Increases in chlorophyll contents and yield attributes in responses to increasing timber-waste biochar in soil were also reported in a biochar trial on wheat crop under greenhouse [75] and laboratory [26] conditions. Similarly, in the current study, the chlorophyll a, chlorophyll b, total chlorophyll, carotenoids, and anthocyanin were significantly increased in response to a higher application rate of PLB (2%; Table 3).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…These strains can be used as inoculants for enhanced crop production, especially in arid environments. Some authors have also reported efficient utilization of ACC deaminase producing rhizobacteria in consortium with biochar [103,104], as well as in combination with plant growth regulators to enhance the yield of wheat plants under drought stress. Spraying of salicylic acid (SA) and putrescine (Put) at the rate of 150 mgL −1 on 25-day old chickpea seedlings in a consortium with PGPR resulted in significantly increased chlorophyll, protein, and sugar contents compared to the well-watered and drought conditions [105].…”
Section: Acc Deaminase Producing Pgpr Ameliorates Water Stress In Plantsmentioning
confidence: 99%
“…PGPR possessing ACC deaminase activity reduce toxicity of heavy metals, drought stress and other abiotic stresses like extreme temperature, salinity and soil pH, besides, antagonism against phytopathogens 76 73 . Leclercia adecarboxylata and Agrobacterium fabrum, Bacillus amyloliquifaciens with higher ACC-deaminase and IAA production traits elevated nutrients uptake and high chlorophyll contents 78,79 . Pseudomonas fluorescens DR7 having high ACC deaminase-and EPS-producing ability increased moisture content in soil and enhanced the root adhering soil and root growth in foxtail millet 80 .…”
Section: Acc Deaminase Production By Rhizobacteriamentioning
confidence: 99%